Participatory video project in Somotillo, Nicaragua - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Project with 15 young farmers in Somotillo, northern-Nicaragua around the themes of climate change and the conservation of the ecosystem. A project in collaboration with CIAT and Humidtropics. Photocredits: Gian Betancourt (CIAT)